(untitled) (Al-Mansour Journal, 2023)
One of the most serious health disasters in recent memory is the COVID-19 epidemic. Several restriction rules have been forced to reduce the virus spreading. Masks that are properly fitted can help prevent the virus from spreading from the person wearing the mask to others. Masks alone will not protect against COVID-19; they must be used in conjunction with physical separation and avoidance of direct contact. The fast spread of this disease, as well as the growing usage of prevention methods, underscore the critical need for a shift in biometrics-based authentication schemes. Biometrics systems are affected differently depending on whether are used as one of the preventive techniques based on COVID-19 pandemic rules. This study provides an overview of biometrics systems and approaches in the post-COVID-19 pandemic. The fundamental COVID-19 prevention rules are first reviewed. The relationships between each regulation and the biometrics that may be impacted are then thoroughly investigated. Recommendations for future trends of feasible approaches are provided to assist researchers in advance and enhance the performance of the biometric system for the post-COVID-19 pandemic environment.